Welcome by the Prime Minister of the Republic of Lithuania at the International Research Conference “Francysk Skaryna and the Renaissance Book Culture. Skaryna’s Little Traveller‘s Book Turns 500” - Šimonytė, Ingrida (Knygotyra, 2023)
Dear organizers and guests of the conference, I would like to share my immense joy that all the crises of recent years did not prevent this international conference Francysk Skaryna and the Renaissance Book Culture – which is of fundamental importance and which bears a highly symbolic meaning, especially today – from taking place in Vilnius. The heroic resistance of Ukrainians against the invaders and their love for freedom attracted the eyes of the entire world to a region which, essentially, had previously been of interest to a tiny fraction of humanity. Thus, attention was directed to the history and relationships between Lithuanians, Belarusians and Ukrainians, to the multicultural heritage of the Grand Duchy of Lithuania which helps us to get to know at a higher level the roots of present-day Europe and to recognize the unique hues of its cultural identity. The first printing press founded in Vilnius five centuries ago launched a new stage of development in the book culture of the region and served as a gate opening up the epoch of Renaissance. The year 2022 was proclaimed by the parliament of the Republic of Lithuania as the year of Francysk Skaryna. This is a profound encouragement to get to know better the intermingled and tightly knit history of the nations of Eastern Europe. In the course of coming back to our European home, we had to learn from our most westerly European neighbours a broad range of things across a wide variety of fields whose natural development had not been interrupted by the Soviet occupation. However, it is essential to acknowledge that Europe is united not only by the mutually accepted rules of economic coexistence or political principles, but also by a multicultural historical heritage. Hence, a more profound understanding of the former region of the Grand Duchy of Lithuania is bound to enrich European ingenuity and creativity. I strongly believe that the insights of this conference will not only be of interest to specialists, but will also serve to advance current, public culture in Lithuania. I sincerely greet everyone, and I am most grateful to everyone who has contributed to holding and hosting this conference, and to all our visitors and guests. May we have insightful discussions that will encourage further research.